2020
DOI: 10.1038/s41467-020-17611-9
|View full text |Cite|
|
Sign up to set email alerts
|

Cosmogenic exposure dating reveals limited long-term variability in erosion of a rocky coastline

Abstract: Predicted sea-level rise and increased storminess are anticipated to lead to increases in coastal erosion. However, assessing if and how rocky coasts will respond to changes in marine conditions is difficult due to current limitations of monitoring and modelling. Here, we measured cosmogenic 10 Be concentrations across a sandstone shore platform in North Yorkshire, UK, to model the changes in coastal erosion within the last 7 kyr and for the first time quantify the relative long-term erosive contribution of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 54 publications
0
34
3
Order By: Relevance
“…Model predictions of CRN concentrations across a shore platform display a characteristic "humped" distribution profile across-shore (Hurst et al, 2017), for which the magnitude of the hump is inversely proportional to cliff retreat rate (Regard et al, 2012). Previous applications of CRN measurements to cliffs and shore platforms have been used to quantify cliff retreat rates (Duguet et al, 2021;Hurst et al, 2016;Regard et al, 2012;Rogers et al, 2012;Swirad et al, 2020), understand Quaternary-scale shore platform exposure history (Choi et al, 2012), date major mass-wasting events (Barlow et al, 2016;Recorbet et al, 2010), and constrain shore platform denudation rates (Raimbault et al, 2018). Combining CRN analysis with a coastal evolution model can help reveal site-specific, long-term cliff retreat and shore platform lowering rates (Trenhaile, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Model predictions of CRN concentrations across a shore platform display a characteristic "humped" distribution profile across-shore (Hurst et al, 2017), for which the magnitude of the hump is inversely proportional to cliff retreat rate (Regard et al, 2012). Previous applications of CRN measurements to cliffs and shore platforms have been used to quantify cliff retreat rates (Duguet et al, 2021;Hurst et al, 2016;Regard et al, 2012;Rogers et al, 2012;Swirad et al, 2020), understand Quaternary-scale shore platform exposure history (Choi et al, 2012), date major mass-wasting events (Barlow et al, 2016;Recorbet et al, 2010), and constrain shore platform denudation rates (Raimbault et al, 2018). Combining CRN analysis with a coastal evolution model can help reveal site-specific, long-term cliff retreat and shore platform lowering rates (Trenhaile, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Today, cliff-retreat rates mostly come from non-weathered cliff erosion (Prémaillon et al, 2018). We can vouch for this assertion based on the millennial retreat rates calculated from 10 Be cosmogenic nuclide (Regard et al, 2012;Hurst et al, 2016;Swirad et al, 2020;Duguet et al, 2021). These millennial rates are either similar to estimates of the current retreat rate (Regard et al, 2012;Swirad et al, 2020) or lower, indicating a recent and gentle acceleration, probably caused by human activity (Hurst et al, 2016;Duguet et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that cliff erosion rates will increase due to rising sea level and possibly increased storminess (Dickson et al 2007;Ashton et al 2011;Trenhaile 2011Trenhaile , 2014aGómez-Pazo and Pérez-Alberti 2017;Limber et al 2018), but the data from hard rock coasts are, at present, ambiguous and contradictory (Lee et al 2001;Hurst et al 2016;Young 2018;Swirad et al 2020). There is little evidence that apparently increasing rates of recession in the study area were triggered by increases in wave height or precipitation, and it is questionable whether such a marked increase in rates could be attributed to an approximately 0.06 m rise in global sea level from 2002 to 2018 (Table 4; Fig.…”
Section: Discussionmentioning
confidence: 99%